Innovative approaches in construction in the context of ukraine's recovery based on the principles of sustainable development - Humenna, Oleksandra (Ways to Improve Construction Efficiency, 2024)
Abstract. The article analyzes modern innovative approaches to construction that are highly relevant for Ukraine’s post-war recovery based on the principles of sustainable development. Considering the large-scale destruction of infrastructure and housing stock caused by military aggression, the author emphasizes the need to rethink traditional development models and shift toward environmentally responsible, energy-efficient, and socially oriented construction practices. The study outlines the main challenges facing the Ukrainian construction sector: high levels of CO₂ emissions, aging infrastructure, low energy efficiency, a shortage of affordable housing, and the urgent need for rapid restoration of damaged facilities. The purpose of the article is to develop a systematic understanding of innovative technologies that support the achievement of sustainable development goals in Ukraine’s construction sector – particularly through the implementation of digital solutions (BIM, 3D printing, drones), the use of energy-efficient materials, the smart building concept, biomimicry, and modular construction. The research methodology is based on systemic, comparative, and analytical approaches, SWOT analysis, and content analysis of strategic documents such as the UN 2030 Agenda for Sustainable Development, the European Green Deal, and Ukraine’s Recovery Plan. The author systematizes sustainability criteria for local communities (attractiveness, environmental safety, adaptability, social cohesion, etc.) and demonstrates how the construction industry can serve as a tool for achieving each of them. The findings show that the implementation of innovations in construction contributes not only to Ukraine’s physical recovery but also to the foundations of socio-economic transformation, reduced dependence on fossil fuels, increased environmental awareness, and the development of resilient local communities. The novelty of the article lies in its integrative approach to assessing innovations in construction as a component of national recovery strategy and long-term development.